Development of a mindfulness–stress–performance model for construction workers. Issue 2 (1st February 2016) - Leung, Mei-yung; Liang, Qi; Yu, Jingyu
Abstract : Construction workers contribute to the success of projects on sites full of hazards and risks. Working in the construction industry is very stressful for them, while stress can impair their performance and safety. Mindfulness has been regarded as effective to manage stress and improve performance in general, while there is constant argument on the mindfulness characteristics. In addition, the effect of individual mindfulness characteristics on construction workers' stress and performance still remains unknown. Therefore to fill in the research gap, a questionnaire survey was administered among construction workers. Nine mindfulness characteristics (framed into three theoretical categories), three stress types and three kinds of performance were identified. The results show that mindfulness characteristics indirectly improve construction workers' performance by relieving their stress: (1) objective stress is mitigated by observation; (2) emotional stress is relieved by observation and awareness, and impairs construction workers' organizational performance; and (3) physical stress is reduced by awareness, and worsens safety performance. Mindfulness characteristics also directly improve construction workers' performance, namely description and observation enhance working performance; and awareness improves safety performance. However, the study interestingly found that the mindfulness attitude group has no effect on construction workers' stress and performance, while decentering even harms their safety performance. The implications underlying the findings are discussed. Several recommendations are made for mitigating stress and improving performance. The mindfulness characteristics are grouped into theoretical categories, and the effects of each mindfulness characteristic on the stress and performance of construction workers are identified.